Treatment adherence and its determinants among the rheumatic fever/rheumatic heart disease patients during COVID 19 pandemic – A cross sectional study from Chandigarh, India - Divya Ilanchoorian; J. S. Thakur; Rajesh Vijayvergiya; Ankur K. Jindal; Aravind Gandhi; Vivek Sagar (Journal of Family Medicine and Primary Care)
Background: Rheumatic heart disease/Rheumatic fever is a non – communicable disease being a major neglected health problem. Recurrent attacks of rheumatic fever can have catastrophic outcomes, therefore regular administration of antibiotics is recommended. During COVID 19 pandemic, people were afraid to approach hospitals hence the compliance and follow up of patients were affected. This study had planned to assess the treatment adherence of patients diagnosed with rheumatic fever/rheumatic heart disease during COVID 19 pandemic and to describe the socio demographic factors, clinical characteristics. This study also determines the factors associated with the treatment adherence. Methods: A cross sectional study was conducted among Rheumatic Fever/Rheumatic Heart Disease patients, attending Outpatient department at tertiary care hospital during COVID 19 pandemic. Mean score with confidence interval was calculated for quantitative data. P value less than 0.05 is significant. Results: The Mean (SD) age of the study participants was 41 ± 14.17 years. Treatment adherence was found to be 94.5 percent among Rheumatic Fever/Rheumatic Heart Disease patients during COVID 19 pandemic. 89.5% of injection benzathine penicillin users had an adherence rate above 80 percent. It was found that the presence of comorbidities (Diabetes/Hypertension/both Diabetes and Hypertension) had a statistically significant association with treatment adherence. Conclusions: Rheumatic Heart Disease is a disease of young and middle -age population affecting predominantly females. The overall adherence rate among Rheumatic Fever/Rheumatic Heart Disease patients was high. High time to maintain hospital-based registry to have follow up of patients.